Secrecy Rate in BD-RIS-Assisted Uplink Multi-User MIMO Systems Under Nakagami-m Fading with Passive Eavesdropping (Journal of Engineering, 2025)
With the evolution toward 6G wireless networks, ensuring secure communication has become increasingly important due to persistent risks of eavesdropping and unauthorized access. Beyond Diagonal Reconfigurable Intelligent Surfaces (BD-RIS) enhance control over wireless channels by independently manipulating both the phase and magnitude of reflected signals, thereby improving the physical-layer security of wireless communication systems. This paper investigates the performance of a BD-RIS-assisted uplink multi-user MIMO system operating under Nakagami-m fading conditions in the presence of a passive eavesdropper. Specifically, we analyze and compare the achievable sum rate and secrecy rate in scenarios both with and without a direct link between the users and the base station. Through detailed simulations, we demonstrate that BD-RIS achieves an improvement of 8.33% in secrecy rate than conventional diagonal RIS under comparable system parameters. Furthermore, we show that the amount of this enhancement is influenced by key system parameters, including the transmit power, the distance of the eavesdropper from the BD-RIS, and the density of active users within the network.